Oxidative DNA damage in human esophageal cancer: clinicopathological analysis of 8‐hydroxydeoxyguanosine and its repair enzyme. Issue 3 (1st August 2013) - Kubo, N.; Morita, M.; Nakashima, Y.; Kitao, H.; Egashira, A.; Saeki, H.; Oki, E.; Kakeji, Y.; Oda, Y.; Maehara, Y.
Summary Both internal and external oxidative stresses act on DNA and can induce carcinogenesis. 8‐hydroxydeoxyguanosine (8‐OHdG) is an indicator of oxidative stress and it leads to transversion mutations and carcinogenesis. 8‐OHdG is excision‐repaired by 8‐OHdG DNA glycosylase (OGG1). The purpose of this study is to clarify the effect of oxidative DNA damage and repair enzymes on esophageal carcinogenesis. The levels of 8‐OHdG and OGG1 were immunohistochemically evaluated in resected specimens, including squamous cell carcinoma (SCC) in 97 patients with esophageal cancer. Higher levels of 8‐OHdG in normal esophageal epithelium were associated with a higher smoking index (P = 0.0464). The 8‐OHdG level was higher in cancerous areas than in normal epithelia (P = 0.0061), whereas OGG1 expression was weaker in cancerous areas than in normal epithelia (P < 0.0001). An increase of OGG1 expression in normal epithelium was observed as 8‐OHdG levels increased (P = 0.0011). However, this correlation was not observed in cancerous areas. High OGG1 expression in the cytoplasm was related to deeper tumors (P = 0.0023), node metastasis (P = 0.0065) and stage (P = 0.0019). Oxidative DNA damage, which is attributable to smoking as well as disturbances in DNA repair systems, appears to be closely related to esophageal carcinogenesis and its progression.